2021
DOI: 10.1016/j.sjbs.2021.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Traditional ancient Egyptian medicine: A review

Abstract: The ancient Egyptians practiced medicine with highly professional methods. They had advanced knowledge of anatomy and surgery. Also, they treated a lot of diseases including dental, gynecological, gastrointestinal, and urinary disorders. They could diagnose diabetes and cancer. The used therapeutics extended from different plants to include several animal products and minerals. Some of these plants are still used in the present day. Fortunately, they documented their life details by carving on stone, clay, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 108 publications
0
41
0
Order By: Relevance
“…The relationship between humans and nature dates back to the prehistoric ages. The latter supplied the former with food, tools of beauty, and treatment [33,34]. Plants [35,36] and lately microorganisms [37,38] have been extensively screened to explore their healing power.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between humans and nature dates back to the prehistoric ages. The latter supplied the former with food, tools of beauty, and treatment [33,34]. Plants [35,36] and lately microorganisms [37,38] have been extensively screened to explore their healing power.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products have been utilized in different folklores to treat many illnesses since ancient times [1][2][3]. The research in the field of natural product chemistry identified various bioactive metabolites that are engaged with the bioactivities such as diterpenes [4], phenolics [5], sesquiterpenes [6,7], steroids [8], flavonoids [9,10], alkaloids [11], saponins [12][13][14], isochromenes [15], benzofuran glucosides [16], and α-pyrones [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products served for thousands of years as the major source for the basic needs of treatment and food in human life [ 1 , 2 ]. Scientists investigated plants [ 3 , 4 ] and microbes [ 5 , 6 ] to deeply understand the causatives of these powers.…”
Section: Introductionmentioning
confidence: 99%